Analisis Tingkat Pencemaran Nitrat Pada Air Tanah Di Kecamatan Cangkringan, Sleman, Daerah Istimewa Yogyakarta - Atikah Zahidah; Doni Prakasa Eka Putra; Wahyu Wilopo (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aimed to analyze the quality of groundwater and the level of nitrate pollution caused by anthropogenic activities in the Cangkringan District, Sleman Regency, and Yogyakarta Special Region. A total of 17 groundwater samples from dug wells, drilled wells, artesian wells and springs were analyzed to obtain chemical information on groundwater in the form of pH, total dissolved solid (TDS), electrical conductivity (DHL), nitrate (NO3) and chloride. (Cl). Based on WHO drinking water quality standards, groundwater in the study location is still classified as safe for consumption. In terms of spatial distribution, high concentrations of TDS and DHL were associated with land cover, where the high concentration was around the sand mining site on the banks of the Gendol River. Meanwhile, relatively high concentrations of nitrate were found in livestock and residential areas. In areas with forested land cover, the concentration was very low. This proves that anthropogenic activities on the surface greatly control the chemical content of the groundwater. Groundwater pollutant sources in this area were identified as originating from agricultural waste and fertilizers based on Cl (mmol) and NO3/Cl (molar ratio) comparison charts. The research succeeded in providing an initial picture regarding groundwater quality so that it can be used as a basis for sustainable groundwater conservation.